Transcriptional components of anteroposterior positional information during zebrafish fin regeneration - Nachtrab, Gregory (Company of Biologists, 2013)
Many fish and salamander species regenerate amputated fins or limbs, restoring the size and shape of the original appendage. Regeneration requires that spared cells retain or recall information encoding pattern, a phenomenon termed positional memory. Few factors have been implicated in positional memory during vertebrate appendage regeneration. Here, we investigated potential regulators of anteroposterior (AP) pattern during fin regeneration in adult zebrafish. Sequence-based profiling from tissues along the AP axis of uninjured pectoral fins identified many genes with region-specific expression, several of which encoded transcription factors with known AP-specific expression or function in developing embryonic pectoral appendages. Transgenic reporter strains revealed that regulatory sequences of the transcription factor gene alx4a activated expression in fibroblasts and osteoblasts within anterior fin rays, whereas hand2 regulatory sequences activated expression in these same cell types within posterior rays. Transgenic overexpression of hand2 in all pectoral fin rays did not affect formation of the proliferative regeneration blastema, yet modified the lengths and widths of regenerating bones. Hand2 influenced the character of regenerated rays in part by elevation of the vitamin D-inactivating enzyme encoded by cyp24a1, contributing to region-specific regulation of bone metabolism. Systemic administration of vitamin D during regeneration partially rescued bone defects resulting from hand2 overexpression. Thus, bone-forming cells in a regenerating appendage maintain expression throughout life of transcription factor genes that can influence AP pattern, and differ across the AP axis in their expression signatures of these and other genes. These findings have implications for mechanisms of positional memory in vertebrate tissues.